APPLICATION OF CLOUD TECHNOLOGIES IN BLENDED LEARNING METHODS - Kerimbaev , Н.Н.; Jotsov, В.С.; Bolyskhanova , М.Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This article provides an overview of scientific papers on the importance of using cloud technologies. The use of cloud technologies and cloud computing services in higher education is dictated by modern requirements. Currently, one of the tasks set for higher education institutions to improve the field of education is the implementation of blended teaching methods. From this point of view, the article discusses methods and techniques that give advantages in blended learning using modern cloud technologies. It is also reported that cloud technologies can be applied to both traditional education and distance learning. It also covers new directions in the development of processing and storage of data obtained in the field of education using distributed systems and cloud computing. In turn, the use of cloud services will create a unique information and educational platform that meets the requirements of education in the country.